Legal Reconstruction of Food Provision for Correctional Inmates in Fulfilling Human Rights - Hendra Sembiring; Syahranuddin Syahranuddin; Lidya Rahmadhani Hasibuan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The provision of food for inmates is part of the fulfillment of fundamental human rights as regulated in the Regulation of the Minister of Law and Human Rights Number 40 of 2017. However, in its implementation, various problems are still found that require in-depth study to reconstruct the existing system to be more effective in realizing the fulfillment of human rights. This study aims to analyze the implementation of the Regulation of the Minister of Law and Human Rights Number 40 of 2017 in fulfilling human rights in correctional institutions and to formulate an ideal legal reconstruction of the provision of food for inmates to realize the fulfillment of human rights in the future. This study uses a normative legal research method with primary legal materials (legislation related to the provision of food in prisons), secondary (books, journals), and tertiary (legal dictionaries). The analysis was carried out qualitatively to examine the implementation of the policy and formulate an ideal legal reconstruction. The results of the study indicate that the implementation of Permenkumham No. 40/2017 still faces various obstacles including budget constraints, inadequate infrastructure, limited competent human resources, and a less than optimal supervision system. The ideal legal reconstruction includes strengthening the legal basis, developing a sustainable funding system, improving HR competency standards, developing an integrated monitoring system, and utilizing information technology in food management to realize the fulfillment of human rights for correctional inmates.